PHONOLOGICAL DIFFICULTIES FACED BY STUDENTS IN LEARNING ENGLISH - Ahmad Renaldi; Ranni Putri Stefani; Ingatan Gulö (Universitas Negeri Padang, 2016)
Being exposed to English use at campus, the writers were interested in phonological difficulties faced by the students as second language learners of English. The question arised was about what kinds of phonological difficulties the learners are having in their effort to learn and speak English. Underlining this research question was the objective to focus on those difficulties when teaching English to L2 learners of English. In collecting the data needed, the initiation was to conduct a survey on talks, speeches, and presentations made by the students. From the findings, main areas where to focus on were decided. The results were then used to list possible difficult sounds and asked the students to pronounce them. How they pronounced the words were recorded to be analysed. The students were also interviewed in order to have another measurement to determine the difficulties they faced. As the result, most of the phonological problems found were related to consonant sounds such as voiced dental fricative, voiceless dental fricative, voiceless post-alveolar fricative, and voiced alveolar approximant sounds. These are the striking features among other phonological issues found after conducting the research.